2021
DOI: 10.3389/fcell.2021.759813
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Bisulfite Sequencing Reveals DNA Methylation Changes in Zinc Finger Family Genes Associated With KRAS Mutated Colorectal Cancer

Abstract: Background: Colorectal cancer (CRC) is a leading cause of cancer death, and early diagnosis of CRC could significantly reduce its mortality rate. Previous studies suggest that the DNA methylation status of zinc finger genes (ZFGs) could be of potential in CRC early diagnosis. However, the comprehensive evaluation of ZFGs in CRC is still lacking.Methods: We first collected 1,426 public samples on genome-wide DNA methylation, including 1,104 cases of CRC tumors, 54 adenomas, and 268 para-tumors. Next, the most d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Further exploration of the GO enrichment analysis revealed that CENPF functions in the cell cycle through regulating mitosis and microtubule binding in various cancers, for instance, CENPF contributes to the deterioration of adrenocortical carcinoma by affecting the cell cycle [ 14 ]. In the heatmap of the GSEA analysis, several ZNFs were upregulated in the CENPF high group, which belong to the zinc finger transcription factor family and have profound impacts on cancer progression [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ], implying a presumable connection between CENPF and these ZNFs. Additionally, CENPI, a constitutive protein of kinetochore, was synergistically upregulated with CENPF (as GSEA results shown), which specifies localization of CENPF to kinetochores and is essential for chromosome segregation and mitosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further exploration of the GO enrichment analysis revealed that CENPF functions in the cell cycle through regulating mitosis and microtubule binding in various cancers, for instance, CENPF contributes to the deterioration of adrenocortical carcinoma by affecting the cell cycle [ 14 ]. In the heatmap of the GSEA analysis, several ZNFs were upregulated in the CENPF high group, which belong to the zinc finger transcription factor family and have profound impacts on cancer progression [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ], implying a presumable connection between CENPF and these ZNFs. Additionally, CENPI, a constitutive protein of kinetochore, was synergistically upregulated with CENPF (as GSEA results shown), which specifies localization of CENPF to kinetochores and is essential for chromosome segregation and mitosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA was treated with bisulfite. Targeted methylation profiling is applied for methylation measurement for a specific 200–500 bp region 28,29 . Methylation Primer software was used for the primer design of the methylation loci region (Primer F:AGAGATAGTTAGGAATAGGAAGATTTATGAG, Primer R:ACCTACTTAATACAAAAACCCATCTATTC).…”
Section: Methodsmentioning
confidence: 99%
“…Targeted methylation profiling is applied for methylation measurement for a specific 200-500 bp region. 28,29 Methylation Primer software was used for the primer design of the methylation loci region (Primer F:AGAGATAGTTAGGAA-TAGGAAGATTTATGAG, Primer R:ACCTACTTAATA-CAAAAACCCATCTATTC). Two polymerase chain reaction (PCR) amplifications were performed, the first one was a PCR amplification with specific primers for the target region of the bisulfite transformed sample, the sample target region was enriched using the optimized system.…”
Section: Methylome Profilingmentioning
confidence: 99%
“…NGS technologies, however, offer the highest sensitivity since local deep bisulfite sequencing is able to detect DNA methylation on the single‐molecule level 146 . Several potential marker genes have already been screened in different body fluids, formalin‐fixed, paraffin‐embedded (FFPE) and tissue 52,147 . The challenges of highly sensitive methylation detection assays lie in the avoidance of false positives due to the technical variance of bisulfite conversion 148,149 and detection of sparse methylation that can originate from sequencing background noise without relevance for the development of CRC tumors 53 …”
Section: Sensitive Detection Of Dna Methylation In Crcmentioning
confidence: 99%
“…146 Several potential marker genes have already been screened in different body fluids, formalin-fixed, paraffin-embedded (FFPE) and tissue. 52,147 The challenges of highly sensitive methylation detection assays lie in the avoidance of false positives due to the technical variance of bisulfite conversion 148,149 2A,B). 69 The use of sensitive and combined marker panels, including genetic tests, offers great new opportunities for screening and prognostic testing.…”
Section: Sensitive Detection Of Dna Methylation In Crcmentioning
confidence: 99%